Assessment of Biochemical Changes in Date Palm (Phoenix dactylifera L.) Cultivars During Fruit Growth and Ripening (Indian Journal of Arid Horticulture, 2025)
The study on biochemical changes in date palm (Phoenix dactylifera L.) cultivars was conducted at ICAR-Central Institute for Arid Horticulture, Bikaner, during the year 2014. The observations on the growth of fruits were recorded from 15th April till harvesting at 15-day intervals. The assessment of biochemical changes in date palm cultivars Halawy, Khalas, Khadrawy, and Shamran at different stages of growth and maturity showed significant differences among the cultivars.The qualitative characters, such as sugar contents (total, reducing sugars, and non-reducing sugars) and ascorbic acid content, increased from the initial stage to the doka stage of harvesting. In contrast, acidity, protein, tannin content, and antioxidant activity increased at the initial stage but exhibited a decreasing trend at the doka stage of fruit maturity. Percent acidity was found to be minimal in cvs. Halawy and Khalas (0.150%).Ascorbic acid content was highest in cv. Khadrawy (11.22 mg/100g pulp) followed by Khalas (10.61 mg/100g pulp) at the harvesting stage. Sugar contents accumulated gradually during fruit development, and the pattern varied among the four cultivars. Cultivar Halawy showed the highest sugar content (36.30% total sugars, 5.96% non-reducing sugars, and 30.34% reducing sugars). Protein content varied from 1.49% in cv. Khalas to 1.73% in cv. Khadrawy. Tannin content ranged from 0.72% in cv. Halawy to 1.00% in cv. Khalas.Antioxidant activity was recorded highest in cv. Halawy (3.50 mmol TE/g) followed by Khalas (3.21 mmol TE/g). The results revealed that cultivar Halawy is superior in respect of quality parameters, followed by cv. Khalas under hot, arid conditions.
Keywords: Date palm; cultivars; antioxidant activity; sugars; protein; tannin